TAMAN KOTA DI SURABAYA SEBAGAI URBAN PARKS - Muhd. Arief Al Husaini (ATRIUM: Jurnal Arsitektur, 2015)
Title: Urban Parks in Surabaya Surabaya is one of the metropolitan cities in Indonesia. Large cities are generally high mobility and limitations in the city. The limitations related to the urban landscape such as the availability of land, air quality, and social interaction space. It is an impact on the quality of life in the city. In order to achieve the quality of life and the need for interaction space, providing plenty of Surabaya city park. The park has many levels, but to a large city should already have a garden level of urban parks. Therefore, it will be analyzed whether the parks in Surabaya is considered urban parks. Analysis of city park in Surabaya through comparing review of literature on urban parks and facts on the ground. The research of parks uses, parks that can represent surabaya's park, taman bungkul dan taman apsari. The results of the analysis concluded that the park has not belonged to urban parks.